Numerical analysis with algorithms and programming - Saha Ray, Santanu (CRC Press, Taylor & Francis Group, 2016)
Numerical Analysis with Algorithms and Programming is the first comprehensive textbook to provide detailed coverage of numerical methods, their algorithms, and corresponding computer programs. It presents many techniques for the efficient numerical solution of problems in science and engineering.